Arheološka najdišča Ptuja = Archaeological sites of Ptuj Panorama = Panorama - Horvat, Jana (Opera Instituti Archaeologici Sloveniae, 2020)
The hill of Panorama in Ptuj is one of the most important areas of Roman Poetovio. Chance finds and small-scale excavations in the past centuries have revealed the existence of significant archaeological remains that included buildings with numerous rooms and objects dedicated to a variety of deities, the remains of a sanctuary dedicated to the Nutrices, an Early Christian church, an aqueduct and a cemetery. The geophysical investigations have revealed the urban design with a rectilinear grid of streets and building plots.The first few chapters of the book present the history of archaeological research on Panorama, the analytical approaches and the geophysical investigations with the methods employed and the final results. The main chapters correlate the archaeological data of differing quality and nature (chance finds, rescue excavations, old and modern archaeological investigations, geophysical surveys) and locate them with a series of plans. The comprehensive overview is supported by a Catalogue of stone monuments that presents the basic data, descriptions, bibliography, commentary and photographs of the stone objects recovered on Panorama.